Alemtuzumab treatment in Denmark: A national study based on the Danish Multiple Sclerosis Registry. (December 2021) - Theodorsdottir, Asta; Debrabant, Birgit; Magyari, Melinda; Kant, Matthias; Rasmussen, Peter V; Malmberg, Carl-Fredrik; Norberg, Iver A; Hansen, Victoria; Bech, Danny; Schmidt, Mathias F; Schreiber, Karen; Frederiksen, Jette L; et al.
Objective: To investigate clinical outcomes in a real-world setting in the complete population-based cohort of alemtuzumab-treated MS patients in Denmark. Methods: Data were retrieved from The Danish Multiple Sclerosis Registry between 2009 and 2019. Demographic and disease-specific patient parameters related to treatment history, efficacy, and safety outcomes were assessed at baseline and during follow-up visits. Results: A total of 209 patients (78% female) started treatment with alemtuzumab during the study period with 3.1 ± 1.4 years follow-up. After 2 years, 75% of patients were relapse-free compared to 48% the year before alemtuzumab ( p  < 0.001). The annual number of relapses was reduced by 69% in year 4 compared with the year prior alemtuzumab. More active disease before alemtuzumab increased the annual hazard rate for relapse (HR: 2.88, p  < 0.001). The Expanded Disability Status Scale (EDSS) score remained stable or improved in 81% of patients after 2 years. The need for an additional treatment course was associated with higher number of relapses in the year before alemtuzumab (odds ratio (OR) = 1.95, p  = 0.001). Conclusion: In a country with primarily escalation strategy, relapse rate reduction was maintained for 5 years, and EDSS stabilized/improved in majority of patients. Higher relapse rate 1 year before alemtuzumab increased the odds for additional courses. Novel serious AEs were not observed.